If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -15 + 1y = -6 Solving -15 + 1y = -6 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '15' to each side of the equation. -15 + 15 + 1y = -6 + 15 Combine like terms: -15 + 15 = 0 0 + 1y = -6 + 15 1y = -6 + 15 Combine like terms: -6 + 15 = 9 1y = 9 Divide each side by '1'. y = 9 Simplifying y = 9
| 7x-(x-1)=31 | | 5-9k+1+k-2(7-k)=p | | 2(7-x)+2x=510 | | 3x^2-26x=9 | | 38=j-10 | | y=2/9x-3 | | 126=-2(1+8p) | | 8x^2-2x=7x^2-5x+10 | | 5x-2(2x+9)=-21 | | 26+m=110 | | 1/5(d-200)=160 | | 2x-21y-500000=0 | | 7/8(-3-x)=14 | | 2f-8(-4f-7)= | | 9(k+5)+10k=-6(1-6k) | | 8/2k-3=20/4K-7 | | B^20b=-80 | | 3(3n+4)-2(2n+5)= | | -6(8x-1)=-90 | | 2(8p-1)-6(1+2p)=20 | | 6x^3+9x^2+12x= | | 9y-7=4 | | (14x^3)/(21x^7) | | 2x+3(x-2)=126 | | 7+14= | | 23=n/8 | | -3(x-1)(x-1)+6=-200 | | 7-4x=9+8x | | (21x^7)/(14x^3) | | (1-2i)z^2+2z+1=0 | | 9(-3D+4)-7= | | 6x^2-5x=5x^2-7x+24 |